2013
DOI: 10.1016/j.immuni.2013.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Bee Venom Phospholipase A2 Induces a Primary Type 2 Response that Is Dependent on the Receptor ST2 and Confers Protective Immunity

Abstract: SUMMARY Venoms consist of toxic components that are delivered to their victims via bites or stings. Venoms also represent a major class of allergens in humans. Phospholipase A2 (PLA2) is a conserved component of venoms from multiple species and is the major allergen in bee venom. Here we examined how bee venom PLA2 is sensed by the innate immune system and induces a type 2 immune response in mice. We found that bee venom PLA2 induced a T helper type 2 (Th2) cell-type response and group 2 innate lymphoid cell a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
182
1
9

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 178 publications
(197 citation statements)
references
References 45 publications
5
182
1
9
Order By: Relevance
“…Recently, it was demonstrated that selectively secreted endogenous PLA 2 -IID from Tregs promoted the differentiation of Tregs, presumably via the PI3K/Akt/mammalian target of rapamycin pathway, and suppressed proliferation of CD4 + and CD8 + T cells (50). It has been also demonstrated that bvPLA 2 induces Th2 response, which may have contributed to the suppression in the experimental model of PD (35,51). Additionally, an enhanced level of PGE 2 by bvPLA 2 treatment may promote the Th2 response (52).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, it was demonstrated that selectively secreted endogenous PLA 2 -IID from Tregs promoted the differentiation of Tregs, presumably via the PI3K/Akt/mammalian target of rapamycin pathway, and suppressed proliferation of CD4 + and CD8 + T cells (50). It has been also demonstrated that bvPLA 2 induces Th2 response, which may have contributed to the suppression in the experimental model of PD (35,51). Additionally, an enhanced level of PGE 2 by bvPLA 2 treatment may promote the Th2 response (52).…”
Section: Discussionmentioning
confidence: 99%
“…The cells were treated with BV (Sigma-Aldrich, St. Louis, MO), melittin (0.5 mg/ml, Sigma-Aldrich), bvPLA 2 (0.1 mg/ml, Sigma-Aldrich), apamin (0.02 mg/ml, Sigma-Aldrich), and mast cell-degranulating peptide (0.01 mg/ml, Sigma-Aldrich), or with various doses of bvPLA 2 in the presence of plate-bound anti-CD3 (5 mg/ml, BD Biosciences, San Jose, CA) and soluble anti-CD28 (2 mg/ml, BD Biosciences) for 72 h. The inactivated bvPLA 2 was obtained by incubating at 100˚C for 3 h in a plate heater (35). After the sample data were acquired on a FACScalibur flow cytometer (BD Biosciences), the results were generated in graphical and tabular formats using the FlowJo software (Tree Star, Ashland, OR).…”
Section: Cell Culturesmentioning
confidence: 99%
“…As it stands, mast cells are likely to play important evolutionarily conserved roles in immunity beyond their notorious role in allergic diseases. While beneficial mast cell roles have emerged in venom degradation (55,56) and in IgE-mediated protection from lethal doses of venom (57,58), the possible involvement of mast cells in the regulation of innate and adaptive immune responses and their roles as effector cells remain enigmatic.…”
Section: Discussionmentioning
confidence: 99%
“…muciniphila dans l'intestin [10]. Ces observations, et d'autres, soulèvent différentes questions fondamentales qui devront être testées dans des études à large échelle, et pourraient aboutir au développement de nouveaux outils thé-rapeutiques.…”
unclassified
“…Ces expériences démontrent une nouvelle fonction bénéfique du module allergique, et en particulier des IgE spéci-fiques du venin d'abeille, dans la résis-tance de l'hôte à certains composés toxiques de ce venin (Figure 1). Une étude publiée au même moment que la nôtre montre qu'une enzyme du venin d'abeille, la phospholipase A2, est un puissant inducteur d'immunité de type 2 chez la souris, et que cette immunité permet d'améliorer l'hypothermie provoquée par l'injection d'une forte dose de cette même enzyme [10]. Comme que les mastocytes, principales cellules effectrices allergiques, augmentent la défense innée de l'hôte à l'encontre de certains venins en libérant des protéases capables d'en neutraliser les effets toxiques [7,8].…”
unclassified